Effect of Progressive Muscle Relaxation on The Level of Anxiety of Haemodialysis Patients at Muhammad Sani Hospital in Karimun - Rizki Sari Utami Muchtar; Marlian Marlian (IJECA (International Journal of Education and Curriculum Application), 2019)
Chronic kidney disease (CKD) has increased these years. Datas from Muhammad Sani Hospital showed number of patients underwent hemodialysis (HD) were 34 in 2015, and has become 77 in April of 2019. One of the replacement therapy in CKD patient was hemodialysis. HD intended to take over renal function to prolong in improve patient’s quality of life.  Patients who undergo HD will experience anxiety caused by some stressors, such as pain at the location of needle insertion. One of the approach to overcome patients from the pain in HD is a non-farmacologic one, which is progressive muscle relaxation (PMR). This study intended to find the effect of PMR to the anxiety level of HD patients. It was a quantitative study, with a quasi experiment using pre and post test without control. Sampling method was purposive sampling and the size was 20 respondents. We used Hamilton Anxiety Rating Scale (HARS) to detrrmine the level of anxiety, and the intervention was PMR. Paired T-Test was applied, with a normality test (Shapiro Wilk) previously done. We found that the effect of PMR was significant, with a p-value 0,000 (<0,005) and the mean of the anxiety level before and after intervention were respectively 22,65 and 16,30 From all 14 parameters in the questionnaire, from the highest score found in this study were respectively: Sleep Disorder, Depression, Stress, Sensoric related Symptom and Gastrointestinal related Symptoms. Based on this study,there was significant effect of PMR in decreasing the anxiety level, and so it is recommended to use PMR in overcoming anxiety problem in HD patients